Growth mechanisms of interfacial carbides in solid-state reaction between single-crystal diamond and chromium. (1st May 2023) - Liu, Zhuo; Cheng, Wei; Mu, Dekui; Lin, Qiaoli; Xu, Xipeng; Huang, Han
Highlights: Catalytically converted carbon (CCC) is formed before chromium carbide. Diamond lattice relaxation facilitates the nucleation of chromium carbides. Interfacial strain in ripening process of carbides was quasi-quantitively measured. Competitive growth of CCC and Cr7 C3 and Cr3 C2 carbides were examined. Growth morphologies are dependent on crystal orientation of diamond. Abstract: Interfacial bonding is one of the most challenging issues in the fabrication, and hence comprehensively influences the properties of diamond-based metal matrix composites (MMCs) materials. In this work, solid-state (S/S) interface reaction between single-crystal synthetic diamond and chromium (Cr) metal was critically examined with special attention given to unveil the role of crystal orientation in the formation and growth of interfacial products. It has been revealed that catalytically converted carbon (CCC) was formed prior to chromium carbides, which is counterintuitive to previous studies. Cr7 C3 was the first carbide formed in the S/S interface reaction, aided by the relaxation of diamond lattices that reduces the interfacial mismatch. Interfacial Cr7 C3 and Cr3 C2 carbides were formed at 600 and 800 °C, respectively, with the growth preferred on diamond (100) plane, because of its higher density of surface defects than (111) plane. Interfacial strain distribution was quasi-quantitively measured using windowed Fourier Transform-Geometric Phase Analysis (WFT-GPA) analysis and an ameliorated strain concentration was found after the ripening of interfacial carbides. Textured morphologies of Cr3 C2 grown on diamond (100) and (111) planes were perceived after S/S interface reaction at 1000 °C, which is reported for the first time. The underlying mechanisms of Cr-induced phase transformation on diamond surface, as well as the crystal orientation dependent growth of interfacial carbides were unveiled using the first-principles calculation. The formation and growth mechanisms of Cr3 C2 were elucidated using SEM, TEM and XRD analyses. Finally, an approach for tailoring the interfacial microstructure between synthetic diamond and bonding metals was proposed. Graphical abstract: Image, graphical abstract